Egypt's Ramesside Pharaohs and the Persians (Vol. 4, Ages in Alignment Series, Second and Revised Edition) - Sweeney, Emmet John 1955- (Algora Publishing, 2021)
The accepted chronology of ancient Egypt, Persia and Babylonia is wrong to a dramatic degree, with some major historical events mis-dated by several centuries. Modern Egyptologists tell us that Seti I and Ramses II reigned 700 years before the rise of the Medes and Persians, but Emmet Sweeney marshals archeological and linguistic evidence to show that Ramses II's dynasty was terminated by the Persian Conquest of Egypt (525 BC). Matching events, matching biographies, and matching cultural artifacts identify Seti II, hailed by the Egyptians as a warrior and hero, with Inaros, the Egyptian patriot who waged war against Xerxes and was eventually impaled on the orders of Artaxerxes I.